Transcriptome-wide analysis of trypanosome mRNA decay reveals complex degradation kinetics and suggests a role for co-transcriptional degradation in determining mRNA levels - Fadda, Abeer; Ryten, Mark; Droll, Dorothea; Rojas, Federico; Färber, Valentin Lutz Fabian; Haanstra, Jurgen R.; Mercé, Clémentine; Bakker, Barbara M.; Matthews, Keith; Clayton, Christine (Molecular microbiology, 2014)
African trypanosomes are an excellent system for quantitative modelling of post-transcriptional mRNA control. Transcription is constitutive and polycistronic; individual mRNAs are excised by trans splicing and polyadenylation. We here measure mRNA decay kinetics in two life cycle stages, bloodstream and procyclic forms, by transcription inhibition and RNASeq. Messenger RNAs with short half-lives tend to show initial fast degradation, followed by a slower phase; they are often stabilized by depletion of the 5′-3′ exoribonuclease XRNA. Many longer-lived mRNAs show initial slow degradation followed by rapid destruction: we suggest that the slow phase reflects gradual deadenylation. Developmentally regulated mRNAs often show regulated decay, and switch their decay pattern. Rates of mRNA decay are good predictors of steady state levels for short mRNAs, but mRNAs longer than 3 kb show unexpectedly low abundances. Modelling shows that variations in splicing and polyadenylation rates can contribute to steady-state mRNA levels, but this is completely dependent on competition between processing and co-transcriptional mRNA precursor destruction.